KOMUNITAS MAKROZOOBENTOS DI SUNGAI PERCUT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG SUMATERA UTARA Macrozoobentos Community in Percut River, Percut Sei Tuan District, Deli Serdang Regency, North Sumatera - David Putra P Situmorang; Hasan Sitorus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Percut river is one of the rivers that flow in Deli Serdang which release into Malaka Straits. The objective of the research were to determine the macrozoobentos community structure and relation of chemical and physical parameters of water to diversity index and family biotic index of macrozoobentos in Percut River, Deli Serdang Regency. The research was conducted by using purposive random sampling method in four stations and four times sampling period on July until August. Physical and chemical parameters observed were temperature, flow rate, turbidity, TSS, pH, DO, BOD5, TOM and substrat structure. Based on the research was found 12 genera of macroozoobenthos as Branchiura, Tubifex, Penaeus, Scylla, Anadara, Melanoides Thiara, Elimia, Pleurocera, Filopaludina, Nerita dan Pila. The highest density was obtained at around of domestic area of 88.1 ind/m2 and the lowest density at around of agricultural area of 51 ind/m2. The highest diversity index of 1.683 (moderate) was obtained at around of fish landing area, and the lowest diversity index of 1,263 (moderate) was obtained at around of domestic area. Based on the family biotic index indicate that the Percut River not suitable for freshwater aquaculture.Keywords : Makrzoobentos, Community Structure, Percut River